PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN DEVELOPMENT DI TAMBANG BAWAH TANAH DMLZ (DEEP MILL LEVEL ZONE) PT FREEPORT INDONESIA - Norvita Irjadani Douw; M. Syamsul Maarif; Lukman M. Baga (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The purpose of this research is to analyze the factors that affect the improvement of employee work productivity and formulate managerial implication. Primary data were obtained through the questionnaire of 75 respondents obtained by stratified random sampling. The data are analyzed using descriptive analysis and Structural Equation Model (SEM) with Partial Least Squares (PLS)3 program. Research has found the factors that impact significantly on worker productivity are salary, work environment and work experience. The managerial implications based on this study are optimize employee salaries structures, repairing communication system at the field, conducting individual work rotation between section, inculuding the development of organizations and promotional systems for employees can increase the productivity of worker Development in the DMLZ (Deep Mill Level Zone) mines PT Freeport Indonesia. Keywords: employee work productivity, sem-pls 3, work productivity improvements, underground mine